2020
DOI: 10.3390/antibiotics9050237
|View full text |Cite
|
Sign up to set email alerts
|

High Abundance of Proteobacteria in Ileo-Anal Pouch Anastomosis and Increased Abundance of Fusobacteria Associated with Increased Pouch Inflammation

Abstract: Low diversity intestinal dysbiosis has been associated with inflammatory bowel disease, including patients with ulcerative colitis with an ileo-anal pouch anastomosis. Furthermore, specific Escherichia coli phylogroups have been linked to inflammatory bowel disease. Our aim was to characterize the differences among microbiota and E. coli phylogroups in active and inactive pouchitis. Disease activity was assessed using the modified pouch disease activity index and by fecal calprotectin. Microbiota diversity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The abundance of the phylum Proteobacteria was increased in both patients with a normal functioning pouch and healthy individuals compared to chronic pouchitis patients. Two out of the three chronic pouchitis patients receiving continued long-term treatment with ciprofloxacin and metronidazole had no detection of members of the Bacteroides genera among the most abundant genera, which possibly could be explained by the previous use of antibiotics, as also suggested by Petersen et al [ 31 ].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The abundance of the phylum Proteobacteria was increased in both patients with a normal functioning pouch and healthy individuals compared to chronic pouchitis patients. Two out of the three chronic pouchitis patients receiving continued long-term treatment with ciprofloxacin and metronidazole had no detection of members of the Bacteroides genera among the most abundant genera, which possibly could be explained by the previous use of antibiotics, as also suggested by Petersen et al [ 31 ].…”
Section: Discussionmentioning
confidence: 68%
“…A recent study by Petersen et al [ 31 ] found that ileo-anal pouch anastomosis patients had an increased abundance of the phylum Proteobacteria compared to patients with UC or Crohn’s disease and healthy individuals. Furthermore, a higher abundance of the phylum Fusobacteria was found in pouch patients with a faecal calprotectin level above 500 µg/mg as a measure for an inflamed pouch [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This Special Issue “Pathogenic Escherichia coli : Infections and Therapies” consists of 12 articles, including original research on intestinal pathologies and extraintestinal infections of human and animal origins caused by E. coli [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] and a review on FimH antiadhesive molecules that can be used to treat urinary tract infections caused by uropathogenic E. coli (UPEC) [ 8 ]. Apart from this review, other original articles propose novel approaches to treat and/or prevent E. coli infections.…”
mentioning
confidence: 99%